Re‐evaluation of agar (E 406) as a food additive. (21st December 2016) - ,; Mortensen, Alicja; Aguilar, Fernando; Crebelli, Riccardo; Di Domenico, Alessandro; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Lambré, Claude; Leblanc, Jean‐Charles; Lindtner, Oliver; et al.
Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of agar (E 406) as a food additive. In the European Union (EU), agar (E 406) has been evaluated by the Scientific Committee for Food (SCF) in 1989, who allocated to agar a not specified acceptable daily intake (ADI), and by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) in 1974, who considered very few data to conclude to a not limited ADI. According to the conceptual framework for the risk assessment of certain food additives re‐evaluated under Commission Regulation (EU) No 257/2010, the Panel considered that the safety assessment is limited to the use and use levels received from industry in 7 food categories for which data were considered in this opinion out of the 70 food categories in which agar (E 406) is authorised; an indicative high refined exposure assessment up to 26 mg/kg body weight (bw) per day has been calculated in toddlers at the 95th percentile (non‐brand‐loyal scenario); agar is unlikely to be absorbed unchanged and slightly fermented by intestinal microbiota; sufficient toxicity data were available; there was no concern with respect to the genotoxicity of agar; no carcinogenic effects were reported in carcinogenicity studies in mice and rats at the doses of 4, 500 mg/kg bw per day and 2, 500 mg/kg bw per day, respectively, the highest doses tested; oral intake of agar (4, 500 mg/person corresponding to 64 mg/kg bw per day) was tolerated in humans for 12 weeks without noticeable side effects. Therefore, the Panel concluded that there is no need for a numerical ADI for agar and that there is no safety concern for the general population at the refined exposure assessment for the reported uses of agar as a food additive.